Riwayah of Hafs and Warsh recitation methods: The case of Maqam Ibrahim - Mohd A' Tarahim, Mohd Razali; Sofyuddin, Yusof; Ahmad Zahid, Salleh; Abdillah Hisham, Ab. Wahab; Nor Hafizi, Yusof; Mohd Faiz Hakimi, Mat Idris; Normadiah, Daud; Zulkifli, M.Y (2017)
The recitation of riwayah Hafs and Warsh are two methods of reciting the Quran that are common in contemporary Muslim society. Both methods of recitations have an important relationship in fiqh. This paper reviews the position of the two riwayah Qiraat Mutawatirah, which are recitation of riwayah Hafs and Warsh in fiqh. Analysis is based on wajh Qiraat to examine the differences that have impact on matters of fiqh among the four schools of thoughts. This paper relies on resources such as books of tafsir, hadith, fiqh and history, scientific journals, working papers and other relevant academic materials. The findings indicate the validity of Qiraat as a discipline, and the differences of reciting the Quran that can bring about a significant impact on Quranic interpretations and Islamic legal rulings. This means that differences in reciting the Quran can lead to differences of opinion among Muslim jurists and their rulings, as in the case of Maqam Ibrahim.